The Effect of Exogenous Spermidine Concentration on Polyamine Metabolism and Salt Tolerance in Zoysiagrass (Zoysia japonica Steud) Subjected to Short-Term Salinity Stress - Li, Shucheng; Jin, Han; Zhang, Qiang (Frontiers in Plant Science, 2016)
Salt stress, and particularly short-term salinity stress, is one of the most serious abiotic factors limiting plant survival and growth in China. It has been established that exogenous spermidine (Spd) stimulats tolerance to salt stress in plants. In the present study, two cultivars that are typically grown in China were used. The two zoysiagrass cultivars, exhibiting a sensitive ( cv. Z081) or tolerant ( cv. Z057) salt stress adaptation ability, were subjected to 200 mM salt stress and treated with different exogenous Spd concentrations for 8 days. Polyamine (Put, Spd and Spm) contents and polyamine metabolic enzyme (ADC, ODC, SAMDC, PAO and DAO), malondialdehyde (MDA), H2O2 and antioxidant enzyme activities (superoxide dismutase, catalase, and peroxidase) were measured. The results showed that salt stress induced increases in Spd and Spm contents and the activity of ornithine decarboxylase (ODC), S-adenosylmethionine decarboxylase (SAMDC) and diamine oxidase (DAO) in both cultivars. Exogenous Spd application did not compromise polyamine contents through the regulation of polyamine-degrading enzymes, and an increase in PA synthesis enzymes was observed during the experiment. The application resulted in a tendency for the Spd and Spm contents and the activities of ODC, S-adenosylmethionine decarboxylase (SAMDC), DAO, and antioxidant enzymes to first increase and then decrease in both cultivars with an increase in the exogenous Spd concentration. H2O2 and MDA significantly decreased in both cultivars treated with Spd. With an increase in the exogenous Spd concentration, the Spd + Spm level scores showed positive correlations with polyamine synthesis enzymes (ADC, SAMDC), DAO, antioxidant enzymes (SOD, POD, CAT), while showing negative correlations with H2O2 and MDA in both cultivars.